Programmable logic controllers - Petruzella, Frank D. 1936- (International edition, 2011)
Programmable logic controllers (PLCs) continue to evolve as new technologies are added to their capabilities. The PLC started out as a replacement for hardwired relay control systems. Gradually, various math and logic manipulation functions were added. Today PLCs are the controller of choice for the vast majority of automated processes. PL Cs now incorporate smaller cases, faster CPIs, networking, and various Internet technologies This Fourth Edition of Programmable Logic Controllers continues to provide an up-to-date introduction to all aspects of PLC programming, instalation, and maintenance procedures. No previous knowledge of PLC systems or programming is assumed. As one reviewer of this edition put it: "I honestly believe that someone with little or no background to PLC systems cloud take this book and teach themselves PLCs."